The Greek Community’s Contribution to Batum’s Political, Social and Economic Life, 1860s–1900s - Tchkoidze, Eka (The Historical Review/La Revue Historique, 2022)
Many aspects relating to the Greek diaspora in the Russian Empire from the eighteenth to the first quarter of the twentieth centuries have been researched in detail. Nevertheless, some pieces in this mosaic are less well known. Batum is one of them. Having first settled there in the 1850s, the Greeks of Batum are one of the largest and oldest minorities in the city. As such, they witnessed its transformation from Ottoman to Russian rule and from a small littoral village to a big, charming and cosmopolitan port-city. Batum’s Greeks were actively involved in all spheres of city life, especially in entrepreneurship and politics. This article focuses on the oil and oil-related business activities in which the Greeks were especially successful. Some Greeks were prominent in the town’s life, serving as councillors. The article reveals that the Greeks of Batum had a high educational and cultural level and made a significant contribution to the city’s development. At the same time, they kept their Greek identity, supporting both the Greek church and schools in Batum.